Six-Month Incidence, Persistence, and Factors Associated With Persistence of Anal Human Papillomavirus in Men: The HPV in Men Study - Nyitray, Alan G. (Oxford University Press, 2011)
Background. Although there are limited numbers of incidence and persistence estimates for anal human papillomavirus (HPV) in women and in men who have sex with men (MSM), there are no such reports for men who have sex with women (MSW). Methods. Genotyping was performed on anal samples from men, aged 18–70, from São Paulo, Brazil; Cuernavaca, Mexico; and Tampa, Florida, who provided specimens at enrollment and the 6-month visit of a 4-year prospective study. Eligibility included no history of genital warts or human immunodeficiency virus. A total of 954 MSW and 156 MSM provided evaluable specimens at both visits. Persistence was defined as type-specific infection at each visit. Results. Incident anal infection was common among both MSM and MSW but generally higher for MSM for HPV groups and specific genotypes. A total of 5.1% of MSM and 0.0% of MSW had a persistent HPV-16 infection at the 6-month visit. Cigarette smoking among MSM and age among MSW were associated with persistent infection with any HPV genotype. Conclusions. Although anal HPV infection is commonly acquired by both MSW and MSM, incident events and persistence occurred more often among MSM. Cigarette smoking is a modifiable risk factor that may contribute to HPV persistence among MSM.